Distribuição espacial da qualidade fisiológica e sanitária de sementes de Coffea arabica L. - Trigo, Maria de Fátima Idalina Qualhano (2010)
The coffee is an important social economic activity for small and medium farmers generating wealth and currency into the country, so Brazil stands out as the largest producer and consumer of coffee in the world. However one of the factors capable of under